IMPROVING THE STRATEGIC PLANNING OF THE DEFENSE-INDUSTRIAL COMPLEX CORPORATIONS OF RUSSIA - Katrina B. Dobrova (Модернизация, инновация, развитие)
In this paper, we develop proposals to improve the strategic planning of Russian corporations of the defense-industrial complex. The relevance of the study due to the fact that the methodology for the adaptation of the strategic management of the military-industrial enterprises with substantial scientifi c and technical potential, should take into account a number of features, such as the identifi cation of the features of competition in the future; understanding of the prospects and development opportunities in the medium and long term; assessment of resource potential; impact assessment and risk in the implementation of promising strategies. In the more precise understanding of the strategy as a pattern of behavior aimed at achieving these goals, a set of rules for search and opportunities; strategic plan is seen as a series of specifi c steps and actions that are integrated in space and time, which lead to the transformation of the current position to the desired. We consider the practice of corporate transformation strategies of the world defense industry using a system method. To improve the strategic planning of Russian defense industry corporations it is recommended to apply the strategy of adapting the defense industry companies and their diversifi cation with the civilian sectors. The key vectors of the development strategy of the defense-industrial complex of Russian corporations are defi ned: providing an acceptable investment climate in the sphere of military-technical cooperation; neutralization of threats by the activities of DIC TNCs; creation of their own TNK defense industry and others.